Brachial‐cephalic fistula recovered with drainage for the basilic vein: Case report. Issue 2 (7th May 2015) - Sousa, Clemente Neves; Norton de Matos, António; Rocha, Ana; Almeida, Paulo; Xavier, Eva
Abstract: Vascular access is essential for the implementation of hemodialysis (HD). The arteriovenous fistula (AVF) can be constructed in various locations using various veins. However, the quality of the veins will influence the construction site, as well as the functioning of the AVF. Careful analysis of the vascular network allows options for the development of new fistulas presentations. We present and discuss the case of a woman aged 69 years in HD in which a brachial‐cephalic fistula with drainage to basilic vein was created, through rotation of the cephalic vein on the forearm level. This kind of access serves to prolong the time spent dialyzing through native fistulae, with their reduced complications and greater cost‐effectiveness.